The Influence of Betel Leaf Extract Administration in Enhancing Non-Specific Immunity to Combat Diseases in the Aquaculture Sector (Review) - Muahiddah, Nuri; Alim, Sahrul (Aquaculture Department, University of Mataram, 2023)
This review aims to investigate the impact of betel leaf extract administration in enhancing non-specific immunity in fish within the context of aquaculture. A literature review was conducted to evaluate previous studies, analyze the mechanisms of action of active compounds, and provide practical recommendations for field implementation. The review results indicate that betel leaf extract has antimicrobial potential that can inhibit the growth of bacteria, viruses, and parasitic agents causing diseases in cultured fish. The administration of this extract also stimulates non-specific immune responses, including increased production of immune cells such as macrophages and lymphocytes. The antioxidant effects of compounds in betel leaves provide protection against oxidative stress, enhancing fish resilience to unfavorable environmental conditions. Despite these positive findings, further research is needed to deeply understand the mechanisms of action of active compounds, taking into account environmental factors in betel leaf extract administration. Integration with other disease management strategies and strict monitoring of environmental safety are crucial aspects of practical implementation. In conclusion, the administration of betel leaf extract can be a promising alternative to enhance fish resistance to diseases in aquaculture. Administering betel leaf extract in feed and water can improve survival rates and egg hatching. Collaboration among researchers, farmers, and other stakeholders is necessary to optimize the practical application of these findings, with the goal of enhancing productivity and sustainability in the aquaculture sector as a whole.Top of Form